2021
DOI: 10.1016/j.injury.2020.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Optimal anatomical location for needle chest decompression for tension pneumothorax: A multicenter prospective cohort study

Abstract: Objective: Tension Pneumothorax (TP) can occur as a potentially life threatening complication of chest trauma. Both the 2 nd intercostal space in the midclavicular line (ICS2-MCL) and the 4 th /5 th intercostal space in the anterior axillary line (ICS 4/5-AAL) have been proposed as preferred locations for needle decompression (ND) of a TP. In the present study we aim to determine chest wall thickness (CWT) at ICS2-MCL and ICS4/5-AAL in normal weight-, overweight-and obese patients, and to calculate theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Given the potential benefit paired with high variability of PHND seen in our study, we agree this provides a strong impetus to focus on refining the indications, identification, education, and technique in terms of type of catheter, anatomic position, and role finger thoracostomy to further improve the care of injured patients …”
mentioning
confidence: 67%
“…Given the potential benefit paired with high variability of PHND seen in our study, we agree this provides a strong impetus to focus on refining the indications, identification, education, and technique in terms of type of catheter, anatomic position, and role finger thoracostomy to further improve the care of injured patients …”
mentioning
confidence: 67%
“…The optimal location for NT continues to be debated in the literature [12,13]. Both the second ICS MCL and the fourth/fifth ICS in the anterior axillary line (ICS 4/5-AAL) have been proposed as the preferred locations.…”
Section: Discussionmentioning
confidence: 99%
“…These latter findings bring into question the safety of using longer catheters at alternative sites. [8][9] We used needle decompression in the 2 nd intercostal space (ICS) midclavicular line (MCL) because it is traditional site for needle decompression and is easy to access and entails penetration of pectoral muscles and a variable quantity of subcutaneous tissue with or without oedema and subcutaneous emphysema 1 . Leigh smith study showed a standard 14 gauge (4.5 cm) cannula may not be long enough to penetrate parietal pleura with up to one third of trauma patients having a chest wall thickness greater than 5 cm in the 2nd ICS MCL.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately this site may have an increased risk of lung damage in the supine patient, as gas collects at the highest point and adhesions are most likely in more dependent parts of the lung. 8 Some studies showed the average chest wall thickness on the 2 nd ICS midclavicular line is 38 mm for men and 52 mm for women…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation